The Impact of Corruption on Migration: Evidence from the Western Balkans - Malaj, Visar; Firza, Najada (Migration Letters, 2023)
The fight against corruption remains one of the most fundamental problems for Western Balkans societies and governments. Hiring in the public sector is often determined by networks and clientelism. The exchange of favours and loyalty to a patron are the “normal” ways to access economic opportunities. As a result, a considerable portion of the population considers emigration as the only path to succeed. The main objective of this study is to analyse the impact of corruption on Western Balkan migrant stocks over the years from 2012 to 2020. The selected time period depends mainly on data availability and frequency. A gravity-based equation is developed to explain changes in the number of immigrants living in 31 European destinations. The proposed econometric model confirms the statistical significance of corruption variables in migrant stocks of receiving countries. Individuals tend to move from countries with high levels of corruption and poor governance toward richer and less corrupt destinations.